The impact of educational units according to some cooperative learning strategy patterns in learning some soccer skills for second grade students (Journal of the College of Basic Education, 2024)
The study aimed to design and implement educational units according to the three cooperative learning strategy patterns (overlapping groups, network learning, and the research group) in learning some football skills. To identify the effect of the three cooperative learning strategies (overlapping groups, networked learning, and learning together) in learning some soccer skills for the three experimental research groups. Identifying which of the three styles is best in learning some soccer skills. The second chapter included many theoretical and interrelated studies, and the researcher used experimental research for its suitability to the objectives, hypotheses, and procedures of the research. Division (A) has 30 students, Division (B) has 32 students, and Division (C) has 30 students. As for the research sample, the researcher divided the sample into three research groups, consisting of 10 students for each group. Learning together, the researcher extracted the procedures of homogeneity and equivalence, and one of the most important research procedures is to design three educational units according to the three patterns, at two units per week, with a time of 45 minutes. The post-test was conducted, and the researcher used the statistical bag. The collaborative learning strategy allows for opportunities for students to exercise leadership, and to identify students who need guidance or coaching. Encouraging, and getting to know the weak students. The overlapping group style is the most effective in learning football skills, followed by the network learning style, and then the together learning style. Among the most important recommendations is the emphasis on the use of cooperative learning strategies in its various styles in teaching football skills. The use of a cooperative learning strategy in the style of overlapping groups in scoring and handling, and the use of the network learning style and learning together in rolling and suppression. Emphasis on the use of the cooperative education strategy when teaching middle school students in particular. Because it enhances the spirit of solicitation and teamwork among team members.